XCP-Winf and RCP-Winf: Improving Explicit Wireless Congestion Control - Barreto, Luís (Journal of Computer Networks and Communications, 2015)
Congestion control in wireless networks is strongly dependent on the dynamics and instability of wireless links. Therefore, it is very difficult to accurately evaluate the characteristics of the wireless links. It is known that TCP experiences serious performance degradation problems in wireless networks. Moreover, congestion control mechanisms that rely on network interaction and network parameters, such as XCP and RCP, do not evaluate accurately the capacity and available link bandwidth in wireless networks. In this paper we propose new explicit flow control protocols for wireless mesh networks, based on XCP and RCP. We name these protocols XCP-Winf and RCP-Winf. They rely on the MAC layer information gathered by a new method to accurately estimate the available bandwidth and the path capacity over a wireless network path. The estimation is performed in real time and without the need to intrusively inject packets in the network. These new congestion control mechanisms are evaluated in different scenarios in wireless mesh and ad hoc networks and compared against several new approaches for wireless congestion control. It is shown that both XCP-Winf and RCP-Winf outperform the evaluated approaches, showing its stable behavior and better channel utilization.